2014
DOI: 10.1021/ef500493n
|View full text |Cite
|
Sign up to set email alerts
|

The Bitumen Upgrading of Nigerian Oil Sand by Supercritical Carbon Dioxide Modified with Alcohols

Abstract: The experimental study of bitumen extraction from Nigerian oil sand by supercritical carbon dioxide was carried out using a high-pressure extractor. Fifty grams (50 g) of oil sand was placed into a 100-mL extractor at a temperature of 110 °C and pressures of 50, 60, or 65 MPa for the interaction with pure carbon dioxide or modified by the addition of 3 g of ethanol or 2-propanol in three runs to investigate the co-solvent effect on recovery. The liquid recovery of bitumen, using pure carbon dioxide, was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Hence, a comprehensive investigation on the extracts at the molecular level is needed, especially on the polar and heavy components in source rock and crude oil. A recent paper [20] reported the CO 2 SFE bitumen extraction from oil sand is relevant to the subject matter.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a comprehensive investigation on the extracts at the molecular level is needed, especially on the polar and heavy components in source rock and crude oil. A recent paper [20] reported the CO 2 SFE bitumen extraction from oil sand is relevant to the subject matter.…”
Section: Introductionmentioning
confidence: 99%
“…The vaporizing capacity of SC-CO 2 can be further increased with the addition of cosolvents. For example, the vapor recovery of Halfdan oil was increased by 6–7% with the addition of 7.5% of methanol, acetone, or isopropanol at 60 °C and 30–60 MPa. , Extracting bitumen from oil sand at 110 °C and 50–65 MPa, the outgassing losses reached as much as 30–40% with the addition of water and isopropanol, compared to 0.27% when the oil sand was heated at 120 °C in the oven for 1 h. , …”
Section: Resultsmentioning
confidence: 99%
“…12 Rudyk et al reported that the introduction of ethanol, as a hydrogen bond acceptor, could benefit the extraction of oil with CO 2 under high pressure and increase the solubility of oil in CO 2 . 8,12,13 As mentioned above, the investigation of density and viscosity variation in CO 2 + ethanol binary systems under high pressure and high temperature could provide theoretical foundation and supporting data in unconventional oil and gas development. Generally speaking, a capillary viscometer is widely applied in viscosity measurement, 14 such as falling-ball viscometer, 15 rolling-ball viscometer, 16,17 vibrating-wire viscometer, 18 and rotating-body viscometer.…”
Section: Introductionmentioning
confidence: 94%
“…Meanwhile, the extraction recovery for crude oil in CO 2 could be significantly enhanced with alcohol . Rudyk et al reported that the introduction of ethanol, as a hydrogen bond acceptor, could benefit the extraction of oil with CO 2 under high pressure and increase the solubility of oil in CO 2 . ,, …”
Section: Introductionmentioning
confidence: 99%